Knowledge of Cancer cervix and its causative agents among HIV-infected and HIV-uninfected adolescent women in rural Medical College in Maharashtra, India - Raval, Ravi M.; Patil, Vaibhav B.; Thaware, Pradnya P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: The aim of this study is to examine the knowledge of human papilloma virus (HPV) and cervical cancer among HIV-infected and HIV-uninfected female adolescents attending Antenatal OPD in Department of Obstetrics and Gynecology, Government Medical College, Miraj, Maharashtra, India. Methods: Subjects were recruited randomly from OPD attending patients. A total of 30 subjects, 15 HIV-infected and 15 HIV-uninfected were selected via randomization and completed a measure of HPV knowledge, based on a previously validated instrument. The study took place in December 2017. Results: The overall mean score on the measure for all subjects was 43.3% (S.D. 10.9). There was no significant difference in HPV knowledge between the HIV-infected and HIV-uninfected groups. Based on results from a previous large-scale study using the same validated measure, this sample scored significantly worse on general HPV knowledge than samples from the other studies. Conclusions: Given the limited knowledge of HPV in this sample, there is greater need for education about the prevention of cervical cancer, specifically among high-risk adolescent women.